The injustices of rape: how activists responded to sexual violence, 1950-1980 - Jacquet, Catherine (Gender and American culture, 2019)
"According to Jacquet, anti-rape efforts in the postwar period often built upon one another and were intersectional, even if organizers and reformers did not always know it; she argues that without the struggle produced from these sometimes dueling efforts, the kinds of changes that emerged by the 1980s and 1990s would not have been possible. Along the way, Jacquet also uses the activists' efforts to reveal the difficulty of challenging ingrained racist and sexist beliefs and practices, the unevenness of reform, and the necessity of cross-collaboration"--